2016
DOI: 10.1186/s13287-016-0449-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a teratogenic transcriptome-based predictive test based on human embryonic versus inducible pluripotent stem cells

Abstract: BackgroundHuman embryonic stem cells (hESCs) partially recapitulate early embryonic three germ layer development, allowing testing of potential teratogenic hazards. Because use of hESCs is ethically debated, we investigated the potential for human induced pluripotent stem cells (hiPSCs) to replace hESCs in such tests.MethodsThree cell lines, comprising hiPSCs (foreskin and IMR90) and hESCs (H9) were differentiated for 14 days. Their transcriptome profiles were obtained on day 0 and day 14 and analyzed by compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…For example, when glucose metabolism is less efficient in hypoxic culture, cells may use glutamine for energy. Previous studies have demonstrated that, under normoxic conditions, glutamine is not used as an energy source by MSCs for cell growth; however, there is more glutamine consumption by MSCs in hypoxic culture than in normoxic culture …”
Section: Current Strategies Used To Construct the Bone Marrow Niche Imentioning
confidence: 99%
“…For example, when glucose metabolism is less efficient in hypoxic culture, cells may use glutamine for energy. Previous studies have demonstrated that, under normoxic conditions, glutamine is not used as an energy source by MSCs for cell growth; however, there is more glutamine consumption by MSCs in hypoxic culture than in normoxic culture …”
Section: Current Strategies Used To Construct the Bone Marrow Niche Imentioning
confidence: 99%
“…HiPSC can easily be derived from individuals of different gender and ages, and have recently been used for several toxicological studies and shown to predict for example cardiac toxicity of cosmetic compounds (Chaudhari et al 2018;Luz and Tokar 2018). Their use for predicting developmental toxicity has also been validated, as transcriptome changes during multi-lineage differentiation upon exposure to valproic acid were similar between hESCs and hiPSCs (Shinde et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This initiative further developed the description of a tiered screening strategy and also exemplified the documentation of test compounds (Zimmer et al 2014). Assays resulting from the project demonstrated how omics technologies may be used in a quantitative way for toxicological prediction models (Pallocca et al 2016;Rempel et al 2015;Shinde et al 2015Shinde et al , 2016Shinde et al , 2017Waldmann et al 2017).…”
Section: Introductionmentioning
confidence: 99%